Nutlet morphology and its taxonomic significance in the genus Mentha L. (Lamiaceae) from Turkey - Tarimcilar, Gül; Yilmaz, Özer; Daskin, Ruziye; Kaynak, Gönül (Bangladesh Journal of Plant Taxonomy, 2013)
The nutlet morphology of 11 taxa of Mentha L. (M. pulegium, M. aquatica, M. × piperita, M. x dumetorum, M. spicata subsp. spicata, M. spicata subsp. tomentosa, M. × villoso-nervata, M. longifolia subsp. longifolia, M. longifolia subsp. typhoides, M. × rotundifolia and M. suaveolens) distributed throughout Turkey was investigated by scanning electron microscopy (SEM). The shape of all studied nutlets was broadly oblong or ovoid. Nutlet size ranged from 0.54 to 0.97 mm in length and from 0.37 to 0.66 mm in width. The smallest and biggest nutlets were found in M. × villoso-nervata and M. aquatica, respectively. The Mentha taxa studied can be divided into three groups, based on nut sculpturing type such as distinctly bireticulate, inconspicuously bireticulate and reticulate. This study has shown that some nutlet morphological characteristics can be utilised as additional diagnostic characteristics in delimitations of Mentha at the species and infraspecific levels.